MDC1 counteracts restrained replication fork restart and its loss causes chemoresistance in BRCA1/2-deficient mammary tumors - Liptay, Martin; Barbosa, Joana S.; Gogola, Ewa; Duarte, Alexandra A.; Dibitetto, Diego; Schmid, Jonas A.; Klebic, Ismar; Mutlu, Merve; Siffert, Myriam; Francica, Paola; Salguero, Israel; van de Ven, Marieke; et al. (bioRxiv, 2022)
MDC1 is a key protein in DNA damage signaling. When DNA double-strand breaks (DSBs) occur, MDC1 localizes to sites of damage to promote the recruitment of other factors, including the 53BP1-mediated DSB repair pathway. By studying mechanisms of poly(ADP-ribose) polymerase inhibitor (PARPi) resistance in BRCA2;p53-deficient mouse mammary tumors, we identified a thus far unknown role of MDC1 in replication fork biology. MDC1 localizes at active replication forks during normal fork replication and its loss reduces fork speed. We show that MDC1 contributes to the restart of replication forks and thereby promotes sensitivity to PARPi and cisplatin. Loss of MDC1 causes MRE11-mediated resection, resulting in delayed fork restart. This improves DNA damage tolerance and causes chemoresistance in BRCA1/2-deficient cells. Hence, our results show a role for MDC1 in replication fork progression that mediates PARPi- and cisplatin-induced DNA damage, in addition to its role in DSB repair.